Rancang Bangun Sistem Informasi Perpustakaan Digital Berbasis Human Centered Design (HCD) - Achmad Fadli; Muhammad Rayhan Alvansyah; Rian Dwi Cahyo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid advancement of information technology has encouraged elementary schools to adopt digital systems for managing learning resources, including school libraries. SDN 15 Tangerang still applies a manual library management method, which leads to several issues such as poorly organized loan records, difficulties in locating book data, and low reading interest among students. This study aims to design and develop a digital library information system using the Human Centered Design (HCD) approach, which emphasizes user needs and comfort. The HCD method is implemented through four stages: understanding the context of use, identifying user needs, designing solutions, and evaluating the system. The findings indicate that the developed system improves the efficiency of library management, simplifies the book borrowing and return processes, and provides a better user experience for students and library staff. Therefore, the implementation of an HCD-based digital library information system is expected to support the improvement of literacy and reading interest among elementary school students.